Risk Factors of Domestic Violence in Pregnancy and its Correlation with Mental Health Disorders - Nadia Khoirunnisa Pasaribu (HM Publisher, 2021)
Domestic violence during pregnancy is a neglected & underreported problem having grave consequences. The world health organization (WHO) defines domestic violence as “the range of sexually, psychologically and physically coercive acts used against adult and adolescent women by current or former male intimate partners”. Physical & verbal abuse during pregnancy is a frequent phenomenon encountered by women of both developed and underdeveloped country, belonging to all cultural communities. There is a strong evidence that domestic violence is related to maternal mental health disorders. The aim of this literature study is to find the best available research evidence on risk factors of domestic violence in pregnancy and its correlation to mental health disorders. To achieve the goal of this study, researcher searched for all studies published between January 2010 until August 2021 using the databases such as google scholar and PubMed. The inclusion criteria were studies that describe risk factors of domestic violence in pregnancy and its correlation with maternal mental health and written in English languange. Condition such as mental retardation, substance abuse and pre-existing mental health problems before were excluded from this study. After a long review of the titles and abstracts of 358 studies, 20 studies were identified for potential inclusion in the review. In the end, a total of 10 trials that fulfil researcher criteria were used in this literature review. The number of participants in each study varied, ranged from 300 to 1000 and the characteristics of the sample are similar. Domestic violence against women and mental disorders amongst pregnant women are extremely prevalent in under-resourced, urban areas and ultimately, have detriment al effects on birth outcomes. Mental health disorders are significantly associate d with having experienced domestic violence in pregnancy. High risk population needs to be identified so that preventive strategies can be planned & implemented to stop the violence and improve mental health during pregnancy.